ANALYSIS OF OBE-BASED ASSESSMENT IMPLEMENTATION AT PRIMAKARA UNIVERSITY - Alam, Helmy Syakh; Astina, Made Arya; Artani, Ketut Tri Budi (Erudio Journal of Educational Innovation, 2025)
This study examines the implementation of Outcome-based Education (OBE) principles in assessment practices at Primakara University. OBE emphasizes achieving specific learning outcomes through practical application and deep understanding, preparing students for real-world challenges. The research analyses exam questions from the academic year 2023-2024 to assess alignment with OBE principles, utilizing theories such as Bloom's Taxonomy, Constructivism, and Authentic Assessment. Findings reveal a predominant focus on higher-order thinking skills (HOTS) in assessment questions, particularly in project-based and case-study formats. Recommendations include enhancing alignment with educational goals and optimizing assessment strategies to foster deeper learning and competency development.